Banche multinazionali e teoria economica - H.G. GRUBEL (Moneta e Credito, 2014)
The paper represents a first attempt to develop a general theory of multinational banking capable of explaining the phenomenon with the help of a few price-theoretic principles. Such theorising is useful in the discussion of policy issues raised by the recent rapid growth of multinational banking and by proposed US legislation designed to curb it. The basic analytical question regards the source of comparative advantage. Specifically, the author looks at how a bank abroad can profitably offer lower lending and higher borrowing rates than its domestic competitors and thus attract customers away from them.